Critical appraisal of paroxetine for the treatment of vasomotor symptoms - Carroll DG; Lisenby KM; Carter TL (Dove Medical Press, 2015)
Dana G Carroll,1,2 Katelin M Lisenby,1,2 Tracy L Carter3 1Department of Pharmacy Practice, Harrison School of Pharmacy, Auburn University, Auburn, AL, USA; 2Department of Family Medicine, College of Community Health Sciences, University of Alabama, University Medical Center, Tuscaloosa, AL, USA; 3Department of Pharmacy, DCH Regional Medical Center, Tuscaloosa, AL, USA Background: Vasomotor symptoms (VMS), characterized by hot flashes and night sweats, are the most commonly reported symptoms associated with estrogen deficiency during menopause and occur in up to 70% of women. The goal of treatment is to reduce the frequency and severity of symptoms. Although hormone therapy (HT) is generally recommended as first-line treatment, it is not appropriate for all patients. Antidepressants, specifically selective serotonin reuptake inhibitors, have been evaluated and utilized internationally for alternative treatment for VMS. In 2013, paroxetine mesylate (Brisdelle®) received a US Food and Drug Administration-labeled indication for moderate-to-severe hot flashes, making it the first nonhormonal treatment for VMS associated with menopause. The objective of this review is to critically evaluate available clinical data regarding the efficacy and safety of paroxetine for the treatment of VMS in menopausal women.Methods: MEDLINE, PubMed, and Google Scholar were searched using the keywords paroxetine, vasomotor symptoms, hot flashes, and menopause. Searches were limited to humans, English language, and clinical trial design with a primary outcome of hot flash/vasomotor changes.Results: Paroxetine (hydrochloride and mesylate) has been associated with a 33%–67% reduction in hot flash frequency with 6–12 weeks of treatment compared to 13.7%–37.8% reductions with placebo in patients both with and without a history of breast cancer. It was also associated with significant reductions in hot flash severity. Benefits of treatment persisted through 24 weeks in the study of the longest duration. Most adverse effects reported were of mild-to-moderate severity, with improved tolerability associated with lower doses (7.5–12.5 mg/day).Conclusion: Paroxetine is a safe and effective therapy for the treatment of VMS during menopause. Paroxetine (7.5–12.5 mg/day) should be considered a first-line therapy option for VMS in patients when HT is either inappropriate or intolerable. Keywords: paroxetine, vasomotor symptoms, hot flashes, menopause